PERAN PEMERINTAH DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH DARI INDUSTRI BATU BATA DI KOTA PEKANBARU - Muhammad Dio Dinanja; Erman M (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research is motivated by the large number of brick businesses in Tenayan Raya District, Pekanbaru City, especially in Tuah Negeri and Bencah Lesung Villages. The brick business is expected to be able to increase the local revenue of Pekanbaru City with the active role of the Pekanbaru City government, especially in issuing a legal basis, namely the Mayor Regulation against the brick business license in Pekanbaru City. Many of the brick businesses that have been established still do not have business permits from the Pekanbaru City Government due to the lack of attention and role of the government in dealing with these brick business permits. Thus, brick business owners only take care of permits up to the Tenayan Raya District level. However, in general, a brick business that already has a business license can contribute to increasing the local revenue of the city of Pekanbaru by issuing local levies.The location of this research was carried out at the Industry and Trade Office, the UMKM Service, the Tenayan Raya Sub-District Office, the Tuah Negeri Urban Village Office, the Bencah Lesung Urban Village Office and Bricks Business Actors. The theory used in this research is the theory of fiscal decentralization. This research uses qualitative research. The types of data used in this study are primary data and secondary data obtained through direct interviews with informants who are considered to know and understand problems in the field, documentation and observation.The results of the research found in the field show that the role of the Pekanbaru City government in increasing local revenue from the brick industry in Pekanbaru City is still considered very far from expectations. Until now, the government has not issued a Mayor's Regulation regarding the licensing of bricks in Pekanbaru City, so this makes it difficult for business owners to be able to contribute to increasing PAD in Pekanbaru City. Business owners are still engaged in their own business from starting to open a business, developing a business and building a place of business based on a makeshift license. Even so, not a few bricks are produced by business owners and have been sold to the market following unstable market prices. The role of the government in this case is still considered very far because the business owner is independent in developing the brick industry. Keyword: Role of Industry, Brick Industry, Local Revenue.